Efek Geopolitik Konflik Israel-Palestina 7 Oktober 2023 Terhadap Pergerakan Harga Saham PT Fast Food Indonesia (KFC) - Agustin, Restu Putri; Sulistiyo, Hari; Salsabila, Tri Sugiarti (Peneliti.net, 2026)
The prolonged Israel-Palestine conflict has led to various impacts, one of which is the boycott of products from companies believed to be affiliated with Israel. This study aims to determine the extent of the impact of the boycott on the stock trading of KFC, which is linked to Yum! Brands, a company supporting Israel. A quantitative approach was used, analyzing secondary data on KFC’s stock movements following the boycott announcement. The results show a significant decline in KFC’s stock value, reflecting the market’s reaction to the boycott decision. In conclusion, product boycotts can have a substantial impact on stock trading, particularly for KFC, as a market response to the negative sentiment generated. This study provides further insight into how boycotts can influence global stock markets.